2017
DOI: 10.1002/mrm.27013
|View full text |Cite
|
Sign up to set email alerts
|

Establishing upper limits on neuronal activity–evoked pH changes with APT‐CEST MRI at 7 T

Abstract: PurposeTo detect neuronal activity–evoked pH changes by amide proton transfer–chemical exchange saturation transfer (APT‐CEST) MRI at 7 T.MethodsThree healthy subjects participated in the study. A low‐power 3‐dimensional APT‐CEST sequence was optimized through the Bloch‐McConnell equations. pH sensitivity of the sequence was estimated both in phantoms and in vivo. The feasibility of pH–functional MRI was tested in Bloch‐McConnell‐simulated data using the optimized sequence. In healthy subjects, the visual stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…Finally, no APT or MT changes were detected using CEST-fMRI at higher chemical shifts (Fig. 4b,c ) confirming the recently published APT-fMRI findings 36 and validating that such Z-spectral signals are not contributing to the glucoCEST-fMRI contrast.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, no APT or MT changes were detected using CEST-fMRI at higher chemical shifts (Fig. 4b,c ) confirming the recently published APT-fMRI findings 36 and validating that such Z-spectral signals are not contributing to the glucoCEST-fMRI contrast.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, Khlebnikov et al . recently confirmed that no pH changes could be detected during brain activation using an fMRI method based on APT 36 , known to be highly sensitive to pH and temperature 37 , 38 . In general, in vivo CEST-weighted experiments suffer from poor spectral selectivity because of the intrinsic nature of CEST (targeting inherently broad spectral resonances), but also because of the strong spectral overlapping between several assigned and non-assigned endogenous CEST agents 10 .…”
Section: Discussionmentioning
confidence: 92%
“…Metabolic MRI is a noninvasive technique that can give new insights into understanding cancer metabolism and potentially provide biomarkers to evaluate or monitor treatment plans. Among the different techniques, a method based on chemical exchange saturation transfer (CEST) has attracted great interest recently . This MRI method is a powerful and sensitive technique in which low concentration solutes can be visualized through the water signal.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that use other approaches to measure pH changes in the brain, such as amide proton chemical exchange saturation transfer (APT-CEST), show that it is challenging to measure pH and that the expected pH differences could be smaller than 0.03 pH units. 34 However, the APT-CEST contrast is believed to predominantly originate from intracellular amides. In the current study it was aimed to specifically measure the pH in mitochondrial or extracellular compartments, so pH changes due to activation could be different there.…”
Section: Discussionmentioning
confidence: 99%